Social health among Iranian medical students during COVID-19 pandemic - Maryam Baradaran Binazir; Fariba Heidari (Tabriz University of Medical Sciences, 2023)
Background: It has been experienced that the COVID-19 pandemic affects students' physical and psychological health as well as their mortality risk; therefore, during the COVID-19 pandemic, it is crucial to recognize that medical students' social health is more important than ever before. Methods: This cross-sectional study was conducted on medical students at preclinical and clinical training levels. The population of the study included medical students of the faculty of medicine at Tabriz University of Medical Sciences, Iran. We used the Raosoft sample size calculator. This study was conducted using an online Standardized questionnaire of "Keyes's Social Well-being" and a demographic scale in the Persian language from the 5th to 29th of October, 2020. We applied the Mann-Whitney test to compare mean scores concerning gender, marital status, level of education, and residence. P value<0.05 was considered statistically significant. Results: The current study involved 242 female and 118 male medical students with average ages of 22.54 (SD=2.41) and 22.48 (SD=2.36) respectively. The majority of participants (294) were single; more than half of them (204) lived in the dormitory. The participants had an average social health score of 84.21 (SD=8.34), indicated a low level of social health in this study. Moreover, we found that social health score was associated with education level, residence, gender, and marital status (P<0.05). Conclusion: During the COVID-19 pandemic, it is crucial to provide medical students with appropriate social health programs to improve their quality of life and increase their achievement.